(untitled) (Scientific journal of the Fergana State University, 2025)
In the twenty-first century, the century of science and technology, information and communication technologies have permeated every aspect of the state and society. This directly raises the demand for expertise in this area. As a result, strengthening information and communication students’ listening comprehension capacity is vital for academic success, professional development, critical thinking abilities, and effective collaboration with others.